Fenotipagem e aloimunização eritrocitária em portadores de anemia falciforme atendidos no Hemocentro de Alagoas - Pinto, Patrícia Costa Alves [UNIFESP] (2010)
Objective: To determine the erythrocyte phenotyping in blood donors and patients with sickle cell anemia (SS) assisted at Hemocentro of Alagoas and also the frequency and factors associated with erythrocyte alloimmunization. Methods: Cross-sectional study with 102 patients with sickle cell anemia (SS) and 100 blood donors. This study was approved by the Ethical Committee of the Federal University of São Paulo and by the Ethical Committee of the University of Science of Health of Alagoas. Patients and blood donors were requested to sign an informed consent form prior to enrolment. The following tests were performed: erythrocyte phenotyping by gel centrifugation, Direct antiglobulin test, Indirect antiglobulin test, and detection of irregular antibodies by panels of phenotyped red blood cells. Variables were compared by Mann-Whitney test and c 2 test or exact Fisher test. Factors associate with alloimmunization was analyzed by univariate and multiple logistic regression analysis. Differences were considered significant if p<0.002. Results: The most frequent antigens found in patients and blood donors were: c (93.1% vs. 83.0%), and (96.1% vs. 94.0%), M (82.4% vs. 82.0%), s (92.2% vs. 79.0%), JK(a) (88.2% vs. 82.0), respectively. Significant differences were observed between the frequency of the phenotype of patients and donors in regard to antigens s, FY(a) and JK(b). From 79 transfused patients, 10 (12.7%) presented positive Indirect Coombs. Thirteen alloantibodies were found, 7 from Rh system, 2 from Kell and 4 were not identified. Factors associated with alloimmunization were the period of time between the last transfusion and the data of the test and being submitted to more than 10 red blood cell transfusions. Patients who received more than 10 transfusions presented a likelihood of presenting alloimmunization 16.39 (2.23-120.59) times higher than who received less than 10 transfusions. All patients presented a negative Direct antiglobulin test. Conclusion: The prevalence of alloimmunization in patients with sickle cell anemia was 12.7% with 70% of antibodies belonging to Rh and Kell systems. This study shows the importance of performing erythrocyte phenotyping in blood donors and receptors in order to decrease the risk of alloimmunization.